In vitro proliferation of achondroplastic and normal mouse chondrocytes, before and after basic fibroblast growth factor stimulation - Argentin, G. (Cell Prolif, 2008)
Achondroplasia in mice is a recessive genetic disorder, characterized by disproportionate dwarfism with reduced bone growth. The cause of this chondrodystrophy is unknown. In this study normal and achondroplastic mouse chondrocytes were cultured in monolayer primary culture, their differentiation was verified by immunofluorescence and their growth was compared. The results showed that achondroplastic cells exhibited a higher proliferative activity than control cells of the same age, confirmed also by a thymidine incorporation assay. Furthermore, basic fibroblast growth factor treatment was found to induce a strong increase in growth of normal mouse chondrocytes, while it did not stimulate statistically significant proliferation of achondroplastic mouse cells. We suppose that this different growth rate could play a role in achondroplastic phenotype development.